Vnos kalcija kot dejavnika v preventivi osteoporoze med mladostniki celjske regije - Fokter, Samo K. (Zdravniški vestnik, 2003)
Background. Adolescence is a critical time for bone mineral acquisition and isas such the crucial period for the prevention of osteoporosis. The purpose of the study was to find whether adolescents' calcium intake in Celje region is high enough to attain peak bone mass. Methods. 2Z 7 pupils attending primary school and 434 students attending secondary school participated in an anonymous survey regarding their calcium intake. The acquired data were statistically analysed. Results. Only 77 (11.8%) among 651 teenagers had an optimal daily intake of calcium (>= 1300 mg). The average calcium intake was 828.9 mg per day. The average daily calcium intake for girls was 777.6 mg and for boys 910.0 mg. Calcium intake decreased with the age of the adolescents. The lowest calcium intake was found in those adolescents who were concerned that drinking milk would make them fat. Conclusions. Because of adolescents' sub-optimal intake of calcium there is a probability that osteoporosis will break out in the future. To avoid that, it would be necessary to start inexpensive education programs aimed at teenagers about the importance of the prevention of osteoporosis in adolescence.
Keywords: Adolescenca; Adolescence; ankete; Calcium; Cheese; Dairy Products; food; Food Habits; Jogurt; Kalcij; Milk; mladostniki; Mlečni izdelki; Mleko; Osteoporosis; Osteoporoza; Prehrambene navade; prehrana; Prevention And Control; Questionnaires; Sir; Yogurt